Factors Influencing the Occurrence of Cataracts In Hospital - Patiku, Yudit; Jannah, St Nurfatul; Faisal, Faisal; Hadija, Hadija (PT.Mantaya Idea Batara, 2024)
This study aimed to determine the factors that influence the occurrence of cataracts in the Sheikh Yusuf Hospital, Gowa Regency. The research design used was analytic with a Cross-Sectional Study approach. The study results were obtained using the Observation sheet with a sample of 55 respondents. After conducting research, sampling is done by accidental sampling, and then the data is processed using computer software. The results of the bivariate analysis showed that there was an effect of age on the incidence of cataracts by regression test with t-test obtained a Significant value of 0.001 < 0.05 and Occupational Effect on the incidence of cataracts with t-test obtained a Significant value of 0.000 < 0.05 this study concludes that there is an effect of age on the incidence of cataracts. Cataracts and there is an effect of work on the incidence of cataracts in the Sheikh Yusuf Hospital, Gowa Regency. It is recommended that the hospital be able to provide information to patients to increase patient knowledge about cataracts and cataract surgery.